Specialization of plant–pollinator interactions increases with temperature at Mt. Kilimanjaro. Issue 4 (5th February 2020) - Classen, Alice; Eardley, Connal D.; Hemp, Andreas; Peters, Marcell K.; Peters, Ralph S.; Ssymank, Axel; Steffan‐Dewenter, Ingolf
Abstract: Aim: Species differ in their degree of specialization when interacting with other species, with significant consequences for the function and robustness of ecosystems. In order to better estimate such consequences, we need to improve our understanding of the spatial patterns and drivers of specialization in interaction networks. Methods: Here, we used the extensive environmental gradient of Mt. Kilimanjaro (Tanzania, East Africa) to study patterns and drivers of specialization, and robustness of plant–pollinator interactions against simulated species extinction with standardized sampling methods. We studied specialization, network robustness and other network indices of 67 quantitative plant–pollinator networks consisting of 268 observational hours and 4, 380 plant–pollinator interactions along a 3.4 km elevational gradient. Using path analysis, we tested whether resource availability, pollinator richness, visitation rates, temperature, and/or area explain average specialization in pollinator communities. We further linked pollinator specialization to different pollinator taxa, and species traits, that is, proboscis length, body size, and species elevational ranges. Results: We found that specialization decreased with increasing elevation at different levels of biological organization. Among all variables, mean annual temperature was the best predictor of average specialization in pollinator communities. Specialization differed between pollinator taxa, but was not related to pollinator traits. Network robustness against simulated species extinctions of both plants and pollinators was lowest in the most specialized interaction networks, that is, in the lowlands. Conclusions: Our study uncovers patterns in plant–pollinator specialization along elevational gradients. Mean annual temperature was closely linked to pollinator specialization. Energetic constraints, caused by short activity timeframes in cold highlands, may force ectothermic species to broaden their dietary spectrum. Alternatively or in addition, accelerated evolutionary rates might facilitate the establishment of specialization under warm climates. Despite the mechanisms behind the patterns have yet to be fully resolved, our data suggest that temperature shifts in the course of climate change may destabilize pollination networks by affecting network architecture. Abstract : We studied specialization patterns in plant–pollinator interactions along a 3.4 km elevational gradient on Mt. Kilimanjaro (Tanzania) and demonstrated that specialization decreased with elevation across networks, communities, and pollinator species. Temperature predicted the degree of specialization better than pollinator richness, resource availability, area, or pollinator traits. Despite the mechanisms behind the patterns have yet to be fully resolved, we conclude that temperature shifts in the course of climate change may destabilize pollination networks by affecting network architecture.